Radiochemical Synthesis and Evaluation of (13)N-Labeled 5-Aminolevulinic Acid for PET Imaging of Gliomas - Pippin, Adam B. (ACS Med Chem Lett, 2017)
[Image: see text] The endogenous amino acid, 5-aminolevulinic acid (5-ALA), has received significant attention as an imaging agent, including ongoing clinical trials for image-guided tumor resection due to its selective uptake and subsequent accumulation of the fluorescent protoporphyrin IX in tumor cells. Based on the widely reported selectivity of 5-ALA, a new positron emission tomography imaging probe was developed by reacting methyl 5-bromolevulinate with [(13)N] ammonia. The radiotracer, [(13)N] 5-ALA, was produced in high radiochemical yield (65%) in 10 min and could be purified using only solid phase cartridges. In vivo testing in rats bearing intracranial 9L glioblastoma showed peak tumor uptake occurred within 10 min of radiotracer administration. Immunohistochemical staining and fluorescent imaging was used to confirm the tumor location and accumulation of the tracer seen from the PET images. The quick synthesis and rapid tumor specific uptake of [(13)N] 5-ALA makes it a potential novel clinical applicable radiotracer for detecting and monitoring tumors noninvasively.